Surgical Strategies in Total Colonic Aganglionosis: Primary Pullthrough-Pathway of Care - Stefanie Märzheuser; Felix Schulze; Judith Lindert (MDPI AG, 2024)
Background: Total colonic aganglionosis, as a rare variant of Hirschsprung Disease, still poses challenges to surgeons in terms of diagnosis and management. The optimal preparation for pullthrough is crucial for reconstructive surgery. This study aims to explore our surgical pathway for children with total colonic aganglionosis (TCA) and to describe the prehabilitation necessary to prepare for successful reconstructive pullthrough surgery. Methods: A prospective review of children with TCA receiving an abdominal surgical intervention between 1/22 and 4/24. The cohort included children receiving mapping +/− primary ileoanal pullthrough. An analysis of preoperative, perioperative, and postoperative data, and a short-term follow-up were performed. Results: A total of 18 children with TCA and no prior pullthrough received an abdominal intervention during the 29-month study period, and 5/18 (27.8%) were female. The children had a median of 4 (range 2-7) prior external surgeries; all had a stoma; 6 (33%) children received parental nutrition; 12 children underwent a mapping of the ganglia distribution and bowel length at a median age of 11 months (range 3-54), and in 10 of them, we relocated the stoma. There was a mean involvement of 15 (5-93) cm small bowel aganglionosis, with the remaining mean ganglionic small bowel having a length of 178 cm (110-254). A total of 11 children underwent straight primary ileoanal pullthrough of the stoma site at a median age of 16.7 months (10-133). Conclusions: The timely diagnosis of TCA still challenges the care team, and most children have a rough journey involving several surgeries until their diagnosis is established. The ensure bowel function with an adequate working stoma is the key to enabling enteral nutrition and growth, which are the baseline requirements to undertake a successful pullthrough procedure and restore continuity. Careful perioperative bowel management and parents' active involvement supports children with Hirschsprung Disease achieving the best possible quality of life.